COMPARATIVE ANALYSIS OF GENDER PROGRESSION IN INDONESIAN LITERATURE: BUMI MANUSIA AND ANTOLOGI RASA - R. Hariyani Susanti; Welli Marlisa; Herlinda Herlinda; Aramudin Aramudin (Universitas Muhammadiyah Gorontalo, 2023)
This study investigates the learning and reinforcement of gender roles throughout people's lives and the evolution of women's roles in Indonesia. By conducting a comparative analysis of two novels (Bumi Manusia by Pramoedya Ananta Toer and Antologi Rasa by Ika Natassa) the study explores the depictions of gender progression in Indonesian literature. Specifically, the analysis focuses on how gender roles and expectations have evolved between the era depicted in both literary works. In Bumi Manusia, women are depicted in traditional roles such as prostitutes, mistresses, wives, helpers, and teachers, whereas in Antologi Rasa, women hold positions as respectable as men, highlighting the progress of gender equality in present times. Additionally, the analysis examines the autonomy of the characters in terms of education, career, and family choices, highlighting the freedom women characters have in Antologi Rasa compared to the restrictions placed upon women in Bumi Manusia. The comparison of these novels provides valuable insight into the changing attitudes and roles of women in Indonesian society.